2005
DOI: 10.1113/jphysiol.2004.075028
|View full text |Cite
|
Sign up to set email alerts
|

Feed‐forward inhibition shapes the spike output of cerebellar Purkinje cells

Abstract: Although the cerebellum is thought to play a key role in timing of movements on the time scale of milliseconds, it is unclear how such temporal fidelity is ensured at the cellular level. We have investigated the timing of feed-forward inhibition onto interneurons and Purkinje cells activated by parallel fibre stimulation in slices of cerebellar cortex from P18-25 rats. Feed-forward inhibition was activated within ∼1 ms after the onset of excitation in both cell types. The rapid onset of feed-forward inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
300
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(332 citation statements)
references
References 45 publications
22
300
1
5
Order By: Relevance
“…In a possible scenario repetitive action potentials from the parallel fibers, like those that occur in vivo (18), could activate glutamatergic synapses onto Purkinje cells to produce a short excitation that would put the on-beam Purkinje cells in an up state regardless of their previous state. The feed-forward inhibition that would then follow (31,32) would switch these on-beam Purkinje cells into a down state, whereas off-beam Purkinje cells, that do not receive the short excitation provided by parallel fibers, would switch states. Our experiments using cell-attached recording techniques suggest that although the switch from up to down states would occur in nearly every cell, approximately a third of the off-beam Purkinje cells would switch to an up state.…”
Section: Discussionmentioning
confidence: 99%
“…In a possible scenario repetitive action potentials from the parallel fibers, like those that occur in vivo (18), could activate glutamatergic synapses onto Purkinje cells to produce a short excitation that would put the on-beam Purkinje cells in an up state regardless of their previous state. The feed-forward inhibition that would then follow (31,32) would switch these on-beam Purkinje cells into a down state, whereas off-beam Purkinje cells, that do not receive the short excitation provided by parallel fibers, would switch states. Our experiments using cell-attached recording techniques suggest that although the switch from up to down states would occur in nearly every cell, approximately a third of the off-beam Purkinje cells would switch to an up state.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal summation of parallel fiber EPSPs has also been shown to be controlled through feed-forward inhibition (33). However, when we repeated these tests in coronal slices in the absence of picrotoxin to preserve feed-forward inhibition, TRAM-34 rapidly increased temporal summation of parallel fiber-evoked EPSPs (Fig.…”
Section: Cav3-kca31 Interaction Controls Temporal Summation Of Parallelmentioning
confidence: 99%
“…This is achieved through effective integration of correlated activity onto the PCs which must be able to act as coincidence detector. The precision of time spiking in PCs is strongly regulated by GABAergic synapses through feed-forward inhibition and because effective summation for spike generation of multiple asynchronous PFs inputs can occur within a time window of only a few milliseconds (Mittmann et al, 2005). Therefore, we explored the possibility that fear-related longterm plastic changes may affect this time window and thereby influence the output of the whole neuronal network.…”
Section: Neural Basis Of the Cerebellar Involvement In Learned Fearmentioning
confidence: 99%
“…In several brain structures it has been shown that precisely timed signal processing depends on direct monosynaptic excitation and underlying disynaptic inhibition (feed-forward inhibition) (Pouille andScanziani 2001 andMittmann et al 2005). All theories of timing concerning the cerebellum require that the output of the cerebellar cortex, encoded in the axons of PCs, be precisely tuned in response to sensory stimulation.…”
Section: Neural Basis Of the Cerebellar Involvement In Learned Fearmentioning
confidence: 99%